An investigation into the behavior of disposable face masks in modified bitumen for sustainable transportation pathways - Syahirah Mansor,; Nur Amirah Mohd Zamri,; Zanariah Abd Rahman,; Rozaini Ramli,; Ahmad Kamil Arshad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since December 2019, COVID-19 infection rates have risen considerably, and the virus is currently widespread around the world. Following the COVID-19 outbreak, the production of medical waste has skyrocketed. Disposable face masks are considered medical waste. Alternative measures must be implemented to assist in reducing medical waste disposal, which can result in serious public health problems and have a negative influence on the environment. In this regard, this research was conducted to investigate the effect of disposable face mask (DFM) ash with varied rates ranging from 5% to 20% by weight on bitumen with a 5% increment to be utilised as an alternative material in asphalt pavement. A series of physical and rheological tests were conducted on the bitumen samples to study the behavior of the DFM ash in bituminous material. Overall, the physical and rheological test results revealed that introducing 20% DFM ash to the modified bitumen was unable to achieve the same properties as with the conventional SMA14 asphalt binder. However, the modified bitumen penetration grade PEN 60/70 has improved the properties and quality of the asphalt in the flexible pavement. In addition, utilising the DFM waste in road construction would be a sustainable technique for protecting the environment by minimising face mask waste caused by the COVID-19 epidemic while lowering the pavement’s construction cost. These research findings may be commercialised to generate revenue in the construction industry for sustainable transportation pathways.